O-Acetylated Chemical Reporters of Glycosylation Can Display Metabolism-Dependent Background Labeling of Proteins but Are Generally Reliable Tools for the Identification of Glycoproteins - Darabedian, Narek; Yang, Bo; Ding, Richie; Cutolo, Giuliano; Zaro, Balyn W.; Woo, Christina M.; Pratt, Matthew R. (Frontiers in Chemistry, 2020)
Monosaccharide analogs bearing bioorthogonal functionalities, or metabolic chemical reporters (MCRs) of glycosylation, have been used for approximately two decades for the visualization and identification of different glycoproteins. More recently, proteomics analyses have shown that per-O-acetylated MCRs can directly and chemically react with cysteine residues in lysates and potentially cells, drawing into question the physiological relevance of the labeling. Here, we report robust metabolism-dependent labeling by Ac42AzMan but not the structurally-similar Ac44AzGal. However, the levels of background chemical-labeling of cell lysates by both reporters are low and identical. We then characterized Ac42AzMan labeling and found that the vast majority of the labeling occurs on intracellular proteins but that this MCR is not converted to previously characterized reporters of intracellular O-GlcNAc modification. Additionally, we used isotope targeted glycoproteomics (IsoTaG) proteomics to show that essentially all of the Ac42AzMan labeling is on cysteine residues. Given the implications this result has for the identification of intracellular O-GlcNAc modifications using MCRs, we then performed a meta-analysis of the potential O-GlcNAcylated proteins identified by different techniques. We found that many of the proteins identified by MCRs have also been found by other methods. Finally, we randomly selected four proteins that had only been characterized as O-GlcNAcylated by MCRs and showed that half of them were indeed modified. Together, these data indicate that the selective metabolism of certain MCRs is responsible for S-glycosylation of proteins in the cytosol and nucleus. However, these results also show that MCRs are still good tools for unbiased identification of glycosylated proteins, as long as complementary methods are employed for confirmation.